The Contributions of Prominent Lexicographers to the Development of Arabic–Arabic Dictionaries - M. Jayadi; Zulhaiki Zulhaiki (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
his research investigates the contribution of lexicographers in the development of Arabic-Arabic dictionaries through significant classical works. The main problem addressed is the lack of comprehensive studies that highlight the role of lexicographers in shaping the structure, methodology, and sustainability of Arabic lexicography. The purpose of this study is to examine how their works contributed to the compilation, development, and preservation of the Arabic language across different periods. The study focuses on prominent figures such as Al-Khalil ibn Ahmad with Kitab al-‘Ayn, Fairuzabadi with Al-Qamus al-Muhit, and Ibn Manzur with Lisan al-Arab. Employing a qualitative approach with library research as its primary method, this research collects data from classical dictionaries, relevant scholarly books, and academic articles. This approach enables an in-depth analysis of lexicographers’ contributions in terms of methodology, systematization, and linguistic enrichment. The findings reveal that these lexicographers not only pioneered the organization of Arabic lexicons but also provided foundational systems that influenced subsequent dictionary compilers. Their methods, although varied, maintained rigorous analysis of meanings and usages, thereby establishing a strong tradition in Arabic lexicography. The contribution of their works lies not only in enriching Arabic vocabulary but also in preserving the language as a cultural and intellectual heritage. This study contributes to a better understanding of the historical and linguistic significance of Arabic-Arabic dictionaries.